Chiasma (2017)
Chiasma is a project of artistic creation that evidences the development of an intimate process, as well as, the interest to understand and deepen the notions of gender, duality, body and fear. In Chiasma the body's figuration not only speaks of a particular body, but also seeks to conceive the body as a social fabric, from where we come from and in which we are immersed in, that is, it is like the uterus in which preconceptions are born such as gender and sexuality and which irremediably mold the identity of the individual from the social normativity. So the concept of uterus is transferred to the concept of society as an allegorical field since is the place where the definition of what is right or wrong is generated. Chiasma is the account of the ambivalent feelings of that psychological and emotional body that is uprooted and recognized by not following the guidelines of social norms...